Social cognition in children at familial high-risk of developing an eating disorder - Kothari, Radha; Barona, Manuela; Treasure, Janet; Micali, Nadia (Frontiers in Behavioral Neuroscience, 2015)
Diagnosis of an eating disorder (ED) has been associated with differences in social cognition. To date research investigating social cognition and ED has mainly employed patient and recovered samples. It is therefore unclear whether differences in social cognition are present prior to onset of ED, potentially contributing to development, or whether differences observed are a consequence of the disorder. We aimed to further explore whether individuals at high-risk for ED present social cognition characteristics previously found in ED groups. Methods Our sample was drawn from a population-based cohort, the Avon Longitudinal Study of Parents and Children (ALSPAC). Data on maternal ED behaviors over the lifetime were collected through in-depth clinical interviews (n = 1,128) conducted using the Structured Clinical Interview for DSM disorders (SCID), and were used to categorize mothers according to ED behaviors over the lifetime: Restricting & Excessive Exercising (n = 58), Purging (n = 70), Binge-eating (n = 72), Bingeing and Purging (n = 66), no ED (n = 862). High-risk status of children was determined using these maternal lifetime behavioral phenotypes. Children at high-risk (maternal ED exposure) were compared to children at low-risk (born to mothers with no ED) on three measures of social cognition: the Social Communication Disorders Checklist (n = 922), the faces subtest of the Diagnostic Analysis of Non-Verbal Accuracy (n = 722), and the Emotional Triangles Task (n = 750). Results Children at high-risk for ED showed poorer performance on measures of social cognition compared to children at low-risk. Maternal lifetime binge-eating, and maternal lifetime bingeing and purging were associated with poorer social communication in children (OR: 2.4, 95% CI: 1.0, 5.7, p = 0.05; and OR: 2.7, 95% CI: 1.1, 6.5, p = 0.03 respectively). Maternal bingeing and purging was also found to be associated with differential facial emotion processing and poorer recognition of fear fr